2019
DOI: 10.1108/imds-02-2019-0090
|View full text |Cite
|
Sign up to set email alerts
|

Social media usage and employee’s job performance

Abstract: Purpose This era is an era of social media (SM); thus, it is an essential tool for communication among individuals and organizations. The excessive use of SM by employees has raised many questions about their job performance. Therefore, there is a dire need to investigate the effects of SM use on an employee’s job performance mediated by knowledge exchange. Furthermore, the purpose of this paper is to examine how the organization’s SM rules can moderate the relationship between personal and work-related use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 62 publications
1
45
1
Order By: Relevance
“…Social media is widely used in the workplace as a tool and platform for users to share their opinions and experiences due to its simplicity, ease of use, timeliness and low cost (Jue et al , 2009). Given such benefits, social media platforms have been utilized to support knowledge exchange within organizations (Behringer and Sassenberg, 2015; Jarfar et al , 2019), enhance team and employee performance (Song et al , 2019) and employee agility (Cai et al , 2018). However, there are still some disputes about the pros and cons of social media usage (SMU) in the workplace (Leftheriotis and Giannakos, 2014; Tajudeen et al , 2018; Zhang et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Social media is widely used in the workplace as a tool and platform for users to share their opinions and experiences due to its simplicity, ease of use, timeliness and low cost (Jue et al , 2009). Given such benefits, social media platforms have been utilized to support knowledge exchange within organizations (Behringer and Sassenberg, 2015; Jarfar et al , 2019), enhance team and employee performance (Song et al , 2019) and employee agility (Cai et al , 2018). However, there are still some disputes about the pros and cons of social media usage (SMU) in the workplace (Leftheriotis and Giannakos, 2014; Tajudeen et al , 2018; Zhang et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, survey research conducted on government employees in Harare, Zimbabwe, found that the usage of SNSs at work reduced employee productivity in terms of learning and knowledge (Wushe & Shenje, 2019). In contrast, a study conducted in Pakistan on the employees of public and private sectors demonstrated that personal and work-related use of SNSs could increase employees' productivity through the exchange of knowledge (Jafar, Geng, Ahmad, Niu, & Chan, 2019). Thus, we can formulate the following hypotheses: H 4 : Deviation from work caused by using SNSs decreases productivity.…”
Section: Deviation From Workmentioning
confidence: 99%
“…As suggested by O'Connor, Schmidt, and Drouin ( 2016), through a study carried out on the employees of a Midwestern United States university, that organizations should provide proper training to employees before incorporating the new rules and policies at work, or else such directives induce stress among them and decrease their work outcomes. Similarly, Pakistan-based survey research on the employees of public and private organizations found that restricting the usage of SNSs increased work stress among employees depriving them of the knowledge exchange process, which eventually reduces sharing and obtaining information (Jafar et al, 2019). Also, an Ethiopian study on university teachers concluded that preventing teachers from using SNSs at university would negatively affect their performance inhibiting knowledge sharing and awareness (Tulu, 2017).…”
Section: Policies For Using Snss At Work Placementioning
confidence: 99%
“…Yang and Yang put forward that strategic orientation is an intangible resource of enterprises, because market orientation, technology orientation, entrepreneurship orientation, etc., will bring technological knowledge, marketing technology, management progress, and even production mode progress, which will bring competitive advantage to enterprises in the process of internationalization [22]. Jafar et al put forward that entrepreneurial-oriented companies will not only meet the existing needs of customers, but also actively shape the future needs [23]. Saad et al put forward that the important role of strategy for international new ventures has also been supported by empirical research.…”
Section: Research Statusmentioning
confidence: 99%